2005
DOI: 10.1183/09059180.05.00009503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of viruses on airway diseases

Abstract: There is strong epidemiological evidence that respiratory viral infections are associated with 80-85% of asthma exacerbations in children. There is less evidence in adults, but the available data suggest viruses are associated with around two-thirds to three-quarters of exacerbations in adults. These associations include severe exacerbations requiring hospitalisation. The most common viruses detected in these studies were rhinoviruses, accounting for two-thirds of viruses detected.Asthmatics have increased sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…Consequently it has been suggested that the familiar symptoms associated with 'colds' are mainly the result of indirect effects of the virus. In support of this hypothesis, a number of recent investigations have reported virus-induced increases in the transcription of certain cytokine genes, and increases in the secretion of some cytokines from infected cells (reviewed in Message and Johnston, 2004;Johnston, 2005;Sharma et al, 2006). This induction of pro-inflammatory genes could explain the production successful use of Echinacea, since virus replication is not an important target.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Consequently it has been suggested that the familiar symptoms associated with 'colds' are mainly the result of indirect effects of the virus. In support of this hypothesis, a number of recent investigations have reported virus-induced increases in the transcription of certain cytokine genes, and increases in the secretion of some cytokines from infected cells (reviewed in Message and Johnston, 2004;Johnston, 2005;Sharma et al, 2006). This induction of pro-inflammatory genes could explain the production successful use of Echinacea, since virus replication is not an important target.…”
Section: Introductionmentioning
confidence: 82%
“…Several respiratory viruses, particularly rhinoviruses, influenza virus and respiratory syncytial virus, have been implicated as causative agents in upper respiratory infections and complications, including common colds, as well as exacerbation of disease episodes in chronic conditions of asthma and chronic obstructive pulmonary disease (COPD, Gern and Busse, 1999;Message and Johnston, 2001;Gwaltney, 2002;Johnston, 2005). However, these viruses generally replicate at relatively low levels in epithelial cells, and accordingly cause little or no damage to the nasal epithelium.…”
Section: Introductionmentioning
confidence: 97%
“…Rhinovirus was chosen because of its frequent association with colds and other upper respiratory infections, and because it has often been implicated in exacerbation of asthmatic and allergic symptoms (Message and Johnston, 2001;Gwaltney, 2002;Message and Johnston, 2004;Johnston, 2005). The Echinacea preparations used were an aqueous extract of mixed Echinacea purpurea aerial plant parts, enriched in polysaccharides (labelled E1), and a 55% ethanol extract of the roots of Echinacea purpurea (E2), which contained alkylamides and various caffeic acid derivatives.…”
Section: Echinacea and Gene Array Analysis: Our Experience With A Sysmentioning
confidence: 99%
“…Las infecciones del tracto respiratorio son las infecciones que más comúnmente afectan a los individuos y son responsables de un enorme gasto económico, éstas van desde triviales resfriados comunes hasta severas neumonías 1 .…”
Section: Introductionunclassified